CLASSROOM ENVIRONMENT SUPPORT OF COMMUNICATION FOR DEAF STUDENTS - David Uwumborlame Bunbun; Teddy Afriyie Owusu; Dora Anokye Asare (SocioEdu: Sociological Education, 2023)
This study employed a case study design to explore classroom environment support for communication for deaf students at the University of Education, Winneba. The study sampled 20 participants which comprised ten deaf students, five interpreters, and five lecturers. A one-on-one semi-structured interview was used to collect data from participants. Data was analyzed using themes. Findings from the study revealed that classroom environment support for communication for deaf students involves, the relationship among deaf students, interpreters, and lectures about communication at the lecture hall; the student's participation at the lecture hall. Based on the results from the study, it was recommended that the management of the University of Education, Winneba, and the Department of Special Education should collaborate to ensure a supportive environment for effective classroom communication for deaf students. The Department of Special Education should facilitate continuous professional development seminars and in-service training for lecturers and interpreters on the education of deaf students to enable them to come up with more innovative ways of communicating with deaf students.